“Actividad anti fúngica “in vitro” de aceite esencial y extracto alcoholico de eucalipto “eucalyptus globulus” sobre candida albicans cepa atcc 10231”. - Echeverría Erazo, Adriana Elizabeth (2017)
The research work was carried out in the Biomolecular and Genetic Laboratory of the Faculty of Health Sciences of the National University of Chimborazo during the months April - July 2017. The general objective is to determine the anti fungal activity "in vitro" of oil essential and alcoholic extract of the aromatic plant, Eucalyptus globulus "Eucalyptus", so the inhibitory effect was related in different concentrations. For the essential oil, concentrations of 12,500ppm, 10,500ppm, 8,500ppm, 6,500ppm, 4,500ppm and 2,500 were used; for the alcoholic extract the concentrations of 50,000ppm, 40,000ppm, 30,000ppm, 20,000ppm, 10,000ppm and 5,000ppm on C. albicans strain ATCC 10231. For this purpose it was seeded on Sabouroud agar using the well-diffusion method with the solutions experimental, Fluconazole was used as mycotic, three repetitions of each treatment were performed to obtain a standard measurement, incubated for 18 h at 37 ° C, after which time the diameters of the inhibition halo were read, for statistical analysis The SPSS program and the Duraffourd and Lapraz essential oils scale were used. As a result, we obtained that the essential oil Eucalyptus globulus has inhibitory activity on C. albicans with an average inhibition halo of 11,6mm at 2,500ppm; 10mm at 4,500; 11,3mm at 6,500; 12.3mm at 8,500ppm; 14mm at 4,500ppm and 17mm at 12,500ppm. In contrast, the alcoholic extract has no inhibitory activity since the dimensions of the halos are null, at an average of 0.83mm in 5,000ppm, 1.5mm in 10,000ppm, 1.83mm in 20,000ppm, 2.16 mm at 30,000ppm, 2.33mm at 40,000ppm, 2.83mm at 50,000ppm. It was determined that the essential oil has an inhibitoiy effect on the fungus C. albicans, so that it can be used as an agent in the control of oral candidiasis.